Expanding the capabilities of the DPS lonosonde system - Magnus, Lindsay Gerald (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2001)
The Digisonde Portable Sounder (DPS) is a low power pulse ionosonde capable of recording a wealth of scientific information about the ionosphere. The routine vertical incidence mode, that produces the scaled ionospheric parameters, only records limited Doppler and no precise angle of arrival (AoA) information. The drift mode produces precise scientific information but only limited range information. This thesis explains the operation of the DPS and then examines the drift data by first showing the Doppler velocities (V*) calculated for a fixed frequency ionogram as well as the velocities calculated from an interesting ionospheric disturbance measured with a stepped frequency ionogram and second by illustrating the presence of a variation in the AoA of ionospheric echoes at sunrise. The conclusion of the thesis is that a drift vertical incidence mode be developed to allow the simultaneous measurement of the scaled ionospheric parameters and the precise AoA and full Doppler spectrum information.
Keywords: Ionosondes